Interrogating the Causes of Industrial Apathy in Gombe, North East Nigeria - Misbahu Sa’idu; Aminu Bakari Buba; Ahmed Usman (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This paper examined the factors and actors that coalesced to engender disinterest in the establishment and sustenance of manufacturing industries in Gombe State, North East geopolitical zone of Nigeria. The study adopted a historical method anchored on oral interviews with sixty (60) local manufacturers, and government officials across the eleven local government areas of Gombe state. Secondary sources in forms of published books, journal articles, Newsletters and Annual reports were also used. The result showed that lack of capital, epileptic electricity supply and weak political will constitute the major causes of industrial apathy in Gombe. Other factors include weak maintenance culture, lack of technical knowhow, longer gestation period in reaping the fruits of manufacturing, crisis of confidence and disdain for loans owing to interest attached to it. Finally, the study argues and recommends that prospects for reviving comatose industries and establishing new ones still exist in the study area. This ray of hope is informed by the emergence of participant political culture which could usher strong political will capable of harnessing the huge mineral endowments of the area. Another impetus added to this optimism is the Federal Government of Nigeria’s policy of economic diversification away from dependence on crude oil.